Recent progress of efficient flexible solar cells based on nanostructures. (October 2021) - Zhu, Yiyi; Zhang, Qianpeng; Shu, Lei; Zhang, Daquan; Fan, Zhiyong
Abstract: Flexible solar cells are important photovoltaics (PV) technologies due to the reduced processing temperature, less material consumption and mechanical flexibility, thus they have promising applications for portable devices and building-integrated applications. However, the efficient harvesting of photons is the core hindrance towards efficient, flexible PV. Light management by nanostructures and nanomaterials has opened new pathways for sufficient solar energy harvesting. Nanostructures on top surfaces provide an efficient pathway for the propagation of light. Aside from suppressing incident light reflection, micro-structured back-reflectors reduce transmission via multiple reflections. Nanostructures themselves can be the absorber layer. Photovoltaics based on high-crystallinity nanostructured light absorbers demonstrate enhanced power conversion efficiency (PCE) and excellent mechanical flexibility. To acquire a deep understanding of the impacts of nanostructures, herein, a concise overview of the recent development in the design and application of nanostructures and nanomaterials for photovoltaics is summarized.